Determiner of Poor Sleep Quality in Chronic Kidney Disease Patients Links to Elevated Diastolic Blood Pressure, hs-CRP, and Blood-count-based Inflammatory Predictors - Maulana Antiyan Empitu; Ika Nindya Kadariswantiningsih; Mochammad Thaha; Cahyo Wibisono Nugroho; Eka Arum Cahyaning Putri; Zaky El Hakim; Maulana Muhtadin Suryansyah; Rieza Rizqi Alda; Mohammad Yusuf Alsagaff; Mochammad Amin; Djoko Santoso; Yusuke Suzuki (The Indonesian Biomedical Journal, 2019)
BACKGROUND: Sleep deprivation is strongly associated with cardiovascular disease (CVD) via sympathetic overstimulation and systemic inflammation in general population. However, the significance of poor sleep quality in chronic kidney disease (CKD) is still underexplored.METHODS: This study assessed the sleep quality of 39 with non-dialysis CKD (ND CKD) patients and 25 hemodialysis CKD (HD CKD) patients using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Poor sleeper was defined as individual with PSQI > 5.RESULTS: The prevalence of poor sleeper (30% vs. 60%, p=0.029) and the cummulative PSQI (ND CKD 4.5±4.4, HD CKD 8±6, p=0.038) are different between ND CKD and HD CKD groups. Among the ND CKD, there are association between short sleep duration (< 5 hours per day) with elevated diastolic blood pressure groups (r=0.421, p<0.05); habitual sleep efficiency with platelet-to-lymphocyte ratio (r= 0.532, p<0.0001); daytime dysfunction with increased hs-CRP (r=0.345, p=0.032) and neutrophil-to-lymphocyte ratio (r=0.320, p=0.046). In HD CKD group, a requirement to use sleep medication was associated with elevated highsensitivity C-reactive protein (hs-CRP) level (r=0.434, p=0.030) and decreased monocyte-to-lymphocyte ratio (r=- 0.410, p=0.042); daytime dysfunction was associated with serum hs-CRP (r=0.452, p=0.023).CONCLUSION: This study revealed that some features of poor sleep quality in CKD patients including low sleep efficiency, daytime dysfunction and requirement to use sleep medication were associated with increased diastolic blood pressure, hs-CRP and blood-count-based inflammatory predictors. Thus, this finding prompt to pay closer attention to sleep complaints in the management of CVD risk factors in CKD patients.KEYWORDS: sleep quality, chronic kidney disease, blood pressure, inflammation